1996
DOI: 10.1159/000109891
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Blood Lead Levels on Cognitive Function of Older Women

Abstract: Elevated blood lead concentrations are known to have detrimental effects on neuropsychological function in both children and occupational cohorts of men and women. Although it is generally accepted that lead exposure at low levels is more dangerous for infants and children than for adults, the issue of the lowest level of exposure at which lead causes deleterious health effects in adults is yet to be solved. There is no available data on the role of lead exposure in cognitive dysfunction in nonoccupational coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
56
1
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 30 publications
4
56
1
1
Order By: Relevance
“…Although these observations are convincing, the conclusion that the adult nervous system is no longer sensitive to low concentrations of lead or PCBs may not be true. Muldoon et al (18) found that elderly women with blood lead levels ≥8 µg/L performed more poorly on a cognitive test than women with blood lead levels ≤3 µg/dL. Cognitive decrements have been repeatedly shown after occupational exposure to lead (19).…”
Section: Lead and Pcbs Both Have Similar Effects With Acute And Chronmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these observations are convincing, the conclusion that the adult nervous system is no longer sensitive to low concentrations of lead or PCBs may not be true. Muldoon et al (18) found that elderly women with blood lead levels ≥8 µg/L performed more poorly on a cognitive test than women with blood lead levels ≤3 µg/dL. Cognitive decrements have been repeatedly shown after occupational exposure to lead (19).…”
Section: Lead and Pcbs Both Have Similar Effects With Acute And Chronmentioning
confidence: 99%
“…Perinatal exposure to other substances such as methyl mercury (14), pesticides (15), and polychlorinated biphenyls (PCBs) (16,17) causes similar reductions in IQ and disruption of behavior. Adult exposures to lead (18,19) and PCBs (20) at concentrations that do not cause obvious neuronal cell death have also been reported to reduce cognitive function.…”
mentioning
confidence: 99%
“…Blood lead (B-Pb) concentrations as low as 0.48 pmolll have been associated with adverse effects on behavior and development in children (1). Furthermore, recent data suggest that B-Pb concentrations of about 0.38 pmolll may be associated with decreased cognitive function in postmenopausal women (2).…”
mentioning
confidence: 99%
“…Conceivably, any alterations in barriers' structural or functional integrity may impair the normal brain function. Pb exposure is known to produce irreversible neurotoxicity (Muldoon et al, 1996;Schwartz et al, 2000;Stollery, 1996), particularly in young children (Bellinger, 2004;Bressler et al, 1999;Cory-Schlecta and Schaumburg, 2000). The high vulnerability of children's brain to Pb toxicity could be partly attributed to the less welldeveloped brain barrier system, or a possibly high sensitivity of their BBB to Pb insults.…”
Section: Discussionmentioning
confidence: 99%